Ribosome engineering to promote new crystal forms - Ramakrishnan, V. (2013)
Crystallographic studies of the ribosome have provided molecular details of protein synthesis. However, the crystallization of functional complexes of ribosomes with GTPase translation factors proved to be elusive for a decade after the first ribosome structures were determined. Analysis of the packing in different 70S ribosome crystal forms revealed that regardless of the species or space group, a contact between ribosomal protein L9 from the large subunit and 16S rRNA in the shoulder of a neighbouring small subunit in the crystal lattice competes with the binding of GTPase elongation factors to this region of 16S rRNA. To prevent the formation of this preferred crystal contact, a mutant strain of Thermus thermophilus, HB8-MRCMSAW1, in which the ribosomal protein L9 gene has been truncated was constructed by homologous recombination. Mutant 70S ribosomes were used to crystallize and solve the structure of the ribosome with EF-G, GDP and fusidic acid in a previously unobserved crystal form. Subsequent work has shown the usefulness of this strain for crystallization of the ribosome with other GTPase factors.